2016
DOI: 10.1111/bjop.12226
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the psychology of mobile gambling: A behavioural synthesis

Abstract: This manuscript reviews the extant literature on key issues related to mobile gambling and considers whether the potential risks of harm emerging from this platform are driven by pre‐existing comorbidities or by psychological processes unique to mobile gambling. We propose an account based on associative learning that suggests this form of gambling is likely to show distinctive features compared with other gambling technologies. Smartphones are a rapidly growing platform on which individuals can gamble using s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
46
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(46 citation statements)
references
References 123 publications
(113 reference statements)
0
46
0
Order By: Relevance
“…It is possible that reinforcement and latency can be fine-tuned by designers to elicit the desired behaviour by users, even in the face of unsuccessful, frustrating outcomes. These implications are particularly exacerbated in mobile gambling, where latencies punctuate periods of reinforcement both (a) as part of the nature of smartphone use [16] and (b) directly under the control of the designer using mechanisms to space out reinforcements.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is possible that reinforcement and latency can be fine-tuned by designers to elicit the desired behaviour by users, even in the face of unsuccessful, frustrating outcomes. These implications are particularly exacerbated in mobile gambling, where latencies punctuate periods of reinforcement both (a) as part of the nature of smartphone use [16] and (b) directly under the control of the designer using mechanisms to space out reinforcements.…”
Section: Discussionmentioning
confidence: 99%
“…When applied to gambling's random ratio schedule of reinforcement, there is the potential for an additive risk of harm. What differentiates mobile gambling from other new gambling technologies is its associative basis; whereas it has been shown that the primary risk of internet gambling is to people already addicted to gambling, mobile gambling's behavioural profile suggests a risk towards a wider proportion of the population [16]. However, there is little extant literature on mobile gambling, and no direct research studying the behaviour of the individual while gambling on a mobile phone.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results of this current scoping study demonstrated that in-play betting features could be accessed via a mobile and desktop device in 87.5% of cases of the sport betting websites visited. This increased accessibility to online gambling platforms and the ease of interaction on platforms such as smartphones may accelerate the acquisition of maladaptive learned behaviours such as problem gambling (James et al 2016). Again, further empirical research is required to explore whether technological advances and the ease of access to bet in-play increase the likelihood of a person experiencing gamblingrelated harm.…”
Section: Discussionmentioning
confidence: 99%
“…One way of interpreting this finding, in line with the in-play betting results, is that mobile betting allows for more instantaneous gambling, providing immediate universal access to betting, and simplifying betting procedures by implementing one-touch options or similar (Griffiths 2007;Deans et al 2016b). This type of feature of mobile phone gambling is likely to affect the Bschedule of reinforcement^ (James et al 2017), in this context, the timing and interval between play and reward (Griffiths and Auer 2013). Correspondingly, it has been noted that bookmakers promote mobile betting over other forms of gambling in their advertisements ) by means of overemphasizing the illusion of control that gamblers perceive when using their smartphones to bet (Lopez-Gonzalez et al 2017a).…”
Section: Discussionmentioning
confidence: 99%